Evaluation of Some Heavy Metals Contents in Soil and Tobacco Grown in Sokoto, Nigeria - Al Umar; Yusuf Sarkingobir; Shehu Sarkin Gobir; Sulaiman Aliyu; Umar Tambari; Abdulrahman Hamza (Kaunia: Integration and Interconnection Islam and Science Journal, 2023)
Tobacco is among the major causers/ determinants of morbidities and mortalities in many parts of the world due to its content compounds such as heavy metals. Therefore, it is needful to evaluate heavy metals embedded in the tobacco plant and soil in our localities to divulge information to stakeholders and the public. The objective of this study is to determine the concentrations of for copper, nickel, iron, manganese, zinc, chromium, lead, and cobalt in soils and tobacco parts (root, stem, and leave) from Gwadabawa, Illela, and Sokoto; therewith, atomic absorption spectroscopy analysis using standard methods was carried out. The results indicate, the levels of metals increase from stem to leaves to roots to soils. 00.1-0.62ppm, 0.01-0.52ppm, 0.002-150.0 ppm, 0.2-10.5ppm, 0.20-6.20ppm, 0.01-101.02ppm, 0.01-2.0ppm, 0.00-1.20ppm, are the extent ranges of heavy metals determined in soils, and different parts (root, leave, and stem of the plant (tobacco for copper, nickel, iron, manganese, zinc, chromium, lead, and cobalt respectively. Thus, continuous or acute exposure to tobacco through consumption or inhalation or the likes can subject the people to many detrimental effects.